2021
DOI: 10.1016/j.yebeh.2021.108047
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state EEG for the diagnosis of idiopathic epilepsy and psychogenic nonepileptic seizures: A systematic review

Abstract: Quantitative markers extracted from resting-state electroencephalogram (EEG) reveal subtle neurophysiological dynamics which may provide useful information to support the diagnosis of seizure disorders. We performed a systematic review to summarize evidence on markers extracted from interictal, visually normal resting-state EEG in adults with idiopathic epilepsy or psychogenic nonepileptic seizures (PNES). Studies were selected from 5 databases and evaluated using the Quality Assessment of Diagnostic Accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…Epilepsy is a multiple complications of aSAH, and the main factors for inducing epilepsy are as follows: (1) oxygen-free radicals and glutamate strongly stimulate the brain, resulting in synchronous abnormal discharge [ 11 ]; (2) vasospasm and obvious ischemia; and (3) insula damage, subarachnoid hemorrhage, and brain tissue edema [ 12 ]. In the late stage of subarachnoid hemorrhage, abnormal astrocyte hyperplasia and nerve cell degeneration will occur, which will inhibit network balance and destroy the excitability of normal neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy is a multiple complications of aSAH, and the main factors for inducing epilepsy are as follows: (1) oxygen-free radicals and glutamate strongly stimulate the brain, resulting in synchronous abnormal discharge [ 11 ]; (2) vasospasm and obvious ischemia; and (3) insula damage, subarachnoid hemorrhage, and brain tissue edema [ 12 ]. In the late stage of subarachnoid hemorrhage, abnormal astrocyte hyperplasia and nerve cell degeneration will occur, which will inhibit network balance and destroy the excitability of normal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…discharge [11]; (2) vasospasm and obvious ischemia; and (3) insula damage, subarachnoid hemorrhage, and brain tissue edema [12]. In the late stage of subarachnoid hemorrhage, abnormal astrocyte hyperplasia and nerve cell degeneration will occur, which will inhibit network balance and destroy the excitability of normal neurons.…”
Section: Total=736mentioning
confidence: 99%
“…Automated extraction of new epilepsy markers on routine EEG could lead to reduced rate of misdiagnosis, increased availability in areas without access to an expert neurophysiologist, and more efficient clinical trials. Research on automatic analysis of EEG data is thriving, in part assisted by the recent increase in computational capacities [43][44][45][46][47][48][49][50] . However, automatic analysis of EEG is not mentioned in any of the high-quality clinical practice guidelines systematically reviewed by the ILAE 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EEG signals are characterized by a high temporal resolution, which is crucial for the analysis of fast brain functional dynamics at different frequency ranges (1–4 Hz, delta; 4–8 Hz theta; 8–12 Hz, alpha; 12–30 Hz, beta; and >30 Hz, gamma). On the other hand, various studies in the literature demonstrated the potential use of EEG signals to identify different abnormal brain conditions, including depression [ 10 , 11 , 12 ], seizures [ 13 , 14 , 15 ] and NDD, such as Parkinson’s disease [ 16 , 17 , 18 ] and AD [ 9 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%